Ce0.9Gd0.1O2−δ membranes coated with porous Ba0.5Sr0.5Co0.8Fe0.2O3−δ for oxygen separation - Zhang, C.; Ran, Ran; Pham, Gia; Zhang, Kun; Liu, J.; Liu, Shaomin (Royal Society of Chemistry, 2015)
Robust oxygen ion conducting membranes based on doped ceria oxides can be used as oxygen permeation membranes with a short circuit to provide the required electronic conduction. Previous methods have coated both surfaces of the ion conducting electrolyte membrane with expensive noble metals as the electronic conducting phase to allow the electron shuttling required for oxygen reduction and oxidation to take place between the two membrane surfaces. During operation of the membrane, the atmosphere on the two sides of the membrane is different. The feed side is exposed to air, whereas the permeated side may be exposed to CO2 or reducing gases such as CH4 or H2. At high operating temperatures, such exposure to different gases requires the use of different materials to prepare the membranes, giving opportunities for further optimisation and the reduction of costs. In this work, a novel Ce0.9Gd0.1O2−δ membrane coated on the surface exposed to air with a cost-effective mixed conductive layer of Ba0.5Sr0.5Co0.8Fe0.2O3−δ was developed to deliver a highly stable oxygen flux for use in clean energy applications or as a membrane reactor for chemical synthesis. The membrane coated with Ba0.5Sr0.5Co0.8Fe0.2O3−δ improved the flux of oxygen compared with membranes coated with pure Ag. A triple phase boundary theory is put forward to explain the observed improvement in the oxygen flux.